Tocolytic effect of a selective FP receptor antagonist in rodent models reveals an innovative approach to the treatment of preterm labor - Tos Enrico; Chollet André; Cirillo Rocco (BMC, 2007)
Abstract Background Management of preterm labor by tocolysis remains an unmet medical need. Prostaglandins play a major role in regulation of uterine activity and in molecular mechanisms of human labor and parturition. There is some circumstantial evidence that prostaglandin F2α by action through the prostaglandin receptor subtype FP is effective in key events during labor uterine contraction, rupture of membranes and cervical dilation. This role of FP is briefly reviewed. In this study, we tested the hypothesis that an orally active and selective FP antagonist may arrest labor and delay parturition in animal models. Methods We examined the effects of a small molecule selective antagonist of the FP receptor (AS604872) in inhibition of spontaneous uterine contraction in pregnant rat near term. We tested AS604872 for its ability to delay preterm birth in a mouse model in which the anti-progestin agent RU486 triggered parturition. Results By oral or intravenous dosing AS604872 reduced markedly and dose-dependently the spontaneous uterine contractions in late-term pregnant rats at gestational days 19-21. In pregnant mice, AS604872 delayed the preterm birth caused by RU486 administration. The effect was dose-dependent with a significant increase in the mean delivery time of 16 and 33 hours at oral doses of 30 mg/kg and 100 mg/kg, respectively, in the case of labor triggered at gestational day 14. In both models AS604872 appeared more effective than the β-agonist ritodrine. Conclusion The tocolytic activity displayed by a selective FP receptor antagonist supports a key role for the FP receptor in the pathophysiology of premature birth and demonstrates the therapeutic potential of an FP antagonist for the treatment of preterm labor cases in which uterine hyperactivity plays a dominant role.